Inhibition of Corrosion of Nickel in Nitric Acid by N-Acetyloxindolylidene p-Chlorophenyl Butenolide. - ELHAMID, E.A.; MISBAH, A.A.; KHALIFA., O.R. (Asian Journal of Chemistry, 2010)
The use of N-acetyloxindolylidene-p-chlorophenyl butenolide as inhibitor of the corrosion of nickel in 2M HNO3 solution has been studied at different temperatures. The protection efficiency increases with decreasing temperatures and reaches 76% at 30ºC. The results of the apparent activation energies in the absence and presence of the inhibitor suggest that the inhibitor does not change the mechanism of the rate determining step of the corrosion process. The mechanism of inhibition was proposed on the basis of the formation of a protective film by the inhibitor molecules on the metal surface. Cathodic polarisation curves were measured galvanostatically in 2M HNO3 solution in the absence and presence of different concentrations of the substance at 30ºC, which confirmed the protection efficiency of the substance under investigation.